Prefrontal D1 dopamine signaling is necessary for temporal expectation during reaction time performance - Parker, Krystal L. (2013)
Responses during a simple reaction time task are influenced by temporal expectation, or the ability to anticipate when a stimulus occurs in time. Here, we test the hypothesis that prefrontal D1 dopamine signaling is necessary for temporal expectation during simple reaction time task performance. We depleted dopamine projections to the medial prefrontal circuits by infusing 6-hydroxidopamine, a selective neurotoxin, into the ventral tegmental area (VTA) of rats, and studied their performance on a simple reaction time task with two delays. VTA dopamine depletion did not change movements or learning of the reaction time task. However, VTA dopamine-depleted animals did not develop delay-dependent speeding of reaction times, suggesting that mesocortical dopamine signaling is required for temporal expectation. Next, we manipulated dopamine signaling within the medial prefrontal cortex using local pharmacology. We found that SCH23390, a D1-type dopamine receptor antagonist, specifically attenuated delay-dependent speeding, while sulpiride, a D2-type receptor antagonist, did not. These data suggest that prefrontal D1 dopamine signaling is necessary for temporal expectation during performance of a simple reaction time task. Our findings provide insight into temporal processing of the prefrontal cortex, and how dopamine signaling influences prefrontal circuits that guide goal-directed behavior.